VIRTUALITY AND FAMILY RELATIONSHIPS DURING THE PANDENIA: 2020-2022 - BENITES-MEDINA, Marcela (2024)
The objective of the article is to analyze the effects of virtuality on family dynamics in the popular sectors of metropolitan Lima in the context of the COVID 19 health crisis between the years 2020-2022. The results presented are part of a broader investigation, which was developed using a quantitative approach, the sample consisted of 370 families and the questionnaire was applied to the head of the household. The results indicate that in families, in this context, the traditional distribution of tasks in the home persists, the mother is in charge of cooking and caring for the younger and older members, although the participation of other members in the tasks isobserved. domestic. It was found that the cell phone was the most used technological device to interact with family, friends, and work. Virtuality has led adults to develop digital skills, with young people being the ones who have developed them. Virtuality has transformed family relationships, improving communication between parents and children and with other family members, although some point out that they remain the same.